First‐in‐human development of a pharmacodynamic biomarker for PAC1 receptor antagonists using intradermal injections of maxadilan. Issue 8 (27th May 2022) - Marynissen, Heleen; Buntinx, Linde; Bamps, Dorien; Depre, Marleen; Ampe, Els; Van Hecken, Anne; Gabriel, Kristin; Sands, Steve; Vargas, Gabriel; de Hoon, Jan
Abstract: Maxadilan, a potent vasodilator peptide, selectively activates the PAC1 receptor, a promising target for migraine therapy. Therefore, maxadilan has been suggested as a tool to study the pharmacodynamics (PDs) of PAC1 receptor antagonists. The objectives of this first‐in‐human study were to: (1) determine the safety, tolerability, dose response, and time course of the dermal blood flow (DBF) changes after intradermal (i.d.) injections of maxadilan in the human forearm, and (2) assess the inter‐arm and inter‐period reproducibility of this response. This was a single‐center, open‐label study in healthy subjects, comprising three parts: (1) dose–response ( n  = 25), (2) response duration ( n  = 10), and (3) reproducibility ( n  = 15). DBF measurements were performed using laser Doppler imaging (LDI) up to 60 min postinjection, or up to 5 days for the response duration assessments. To assess reproducibility, the intraclass correlation coefficient (ICC) and sample sizes were calculated. The i.d. maxadilan (0.001, 0.01, 0.1, 0.9, 3, and 10 ng) produced a well‐tolerated, dose‐dependent increase in DBF, with a half‐maximal effective concentration fitted at 0.0098 ng. The DBF response to 0.9 ng maxadilan was quantifiable with LDI up to 72 h postinjection. The inter‐period reproducibility of the DBF response was better upon 0.9 ng (ICC > 0.6) compared to 0.01 ng (ICC < 0.4) maxadilan. However, irrespective of the study design or maxadilan dose, a sample size of 11 subjects is sufficient to detect a 30% difference in DBF response with 80% power. In conclusion, intradermal maxadilan provides a safe, well‐tolerated, and reproducible PD biomarker for PAC1 receptor antagonists in vivo in humans.